The evolution of human rights thinking in North Korea - WEATHERLEY, Robert (Institutional Knowledge at Singapore Management University, 2008)
The official discourse of human rights in North Korea has shown signs of evolution in recent times, reflecting a variety of philosophical foundations and a need to respond to mounting criticism from the West. While Confucianism and Marxism have been key in influencing North Korean rights thinking, some of the more recent official pronouncements on rights have a distinctly nationalistic or ‘juche-oriented’ complexion. This shift in emphasis reflects the growing importance of juche to North Korea's state ideology in light of what is perceived as an increasingly hostile international environment that has confronted North Korea since the end of the Cold War and in particular in consequence of its highly controversial nuclear weapons programme.